1996
DOI: 10.1128/jcm.34.5.1348-1349.1996
|View full text |Cite
|
Sign up to set email alerts
|

IS6110-based PCR methods for detection of Mycobacterium tuberculosis

Abstract: IS6110-Based PCR Methods for Detection of Mycobacterium tuberculosis Kent et al. (3) detected Mycobacterium tuberculosis by a nested PCR test that amplified a 181-bp target located in insertion sequence IS6110, but they also encountered many false-positive results when the test was applied to isolates of mycobacteria that do not belong to the M. tuberculosis complex. Because the investigators attributed the false positives to homology between IS6110 and genomic DNA of the other mycobacterial species, they warn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…In a subsequent study by Hellyer et al (9) no DNA amplification of any of the 27 NTM isolates analyzed, 26 of which had been used in the study by Kent et al (13), was observed. Similar results were obtained by Mulcahy et al (15).…”
supporting
confidence: 92%
“…In a subsequent study by Hellyer et al (9) no DNA amplification of any of the 27 NTM isolates analyzed, 26 of which had been used in the study by Kent et al (13), was observed. Similar results were obtained by Mulcahy et al (15).…”
supporting
confidence: 92%
“…IS elements are highly mobile and capable of spreading among species and genera [5,7]. IS-based PCR methods in some circumstances have been used serendipitously for the detection of organisms other than for which they were originally described, with varying success.…”
Section: Discussionmentioning
confidence: 99%
“…The meningococcal IS1106 PCR has proved to be highly sensitive identifying 91 cases following evaluation during the last quarter of 1995 [4]. Unfortunately the suitability of IS elements for the detection of speci¢c pathogens is compromised by their inherent genetic mobility resulting in potential spread to other species and genera [5]. Subsequently during the evaluation period of the IS1106 PCR enzyme-linked immunosorbent assay (ELISA), a number of cases occurred where organisms other than N. meningitidis were cultured from the blood of patients whose clinical samples repeatedly tested positive in the IS1106 PCR ELISA.…”
Section: Introductionmentioning
confidence: 99%
“…IS elements are highly mobile and capable of spreading among species and genera [5, 7]. IS‐based PCR methods in some circumstances have been used serendipitously for the detection of organisms other than for which they were originally described, with varying success.…”
Section: Discussionmentioning
confidence: 99%
“…The meningococcal IS 1106 PCR has proved to be highly sensitive identifying 91 cases following evaluation during the last quarter of 1995 [4]. Unfortunately the suitability of IS elements for the detection of specific pathogens is compromised by their inherent genetic mobility resulting in potential spread to other species and genera [5]. Subsequently during the evaluation period of the IS 1106 PCR enzyme‐linked immunosorbent assay (ELISA), a number of cases occurred where organisms other than N. meningitidis were cultured from the blood of patients whose clinical samples repeatedly tested positive in the IS 1106 PCR ELISA.…”
Section: Introductionmentioning
confidence: 99%